HAEMATOLOGY OF SALINE TILAPIA (Oreochromis niloticus) FED WITH MORINGA LEAF POWDER ENRICHED PELLETS - Afifah, Nida Farah; Windarti, Windarti; Sarumaha, Herman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Moringa leaves (Moringa oleifera) contain flavonoids and saponins that can help improve fish health. Fish health and immune conditions can be predicted based on fish haematology. The study aimed to determine the effects of powder addition of Moringa leaves in fish feed pellets on the haematological disorders of saline tilapia. It was carried out from July to August 2022. Moringa leaf flour was mixed well with pelleted feed, and the dose of Moringa leaf flour was as follows: 0 (Control, without the addition of Moringa leaves), P1 (10 g/kg), P2 (15 g/kg), and P3 (20 g/kg). Fish were stored in round plastic containers (25 L, equipped with an aerator and circulation pump) for 42 days, 15 fish/container. During the study, fish were fed three times/day at satiation. Sampling was carried out twice, namely before treatment and at the end of the experiment (day 42). The results showed that adding Moringa leaf flour to fish feed pellets affected fish haematology. Fish fed with turmeric-enriched pellets showed a higher percentage of lymphocytes, increasing the fish's immunity. The best treatment was P2, which showed 81.66% lymphocytes, 7.11% monocytes, 8.66% neutrophils, and 2.55% thrombocytes. Data obtained showed that fish fed with Moringa leaf pellets had better haematological conditions than fish not fed with Moringa leaf pellets.